2012
DOI: 10.3389/fncir.2012.00103
|View full text |Cite
|
Sign up to set email alerts
|

Structural plasticity of spines at giant mossy fiber synapses

Abstract: The granule cells of the dentate gyrus give rise to thin unmyelinated axons, the mossy fibers. They form giant presynaptic boutons impinging on large complex spines on the proximal dendritic portions of hilar mossy cells and CA3 pyramidal neurons. While these anatomical characteristics have been known for some time, it remained unclear whether functional changes at mossy fiber synapses such as long-term potentiation (LTP) are associated with structural changes. Since subtle structural changes may escape a fine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 55 publications
0
24
2
Order By: Relevance
“…On the postsynaptic side, we observed an increase in the complexity of the large spines or excrescences in contact with MFBs. In particular, we observed the formation of small, filopodia-like protrusions originating from the large complex spines (Zhao et al, 2012a,b). Thus, the more labyrinthine course of the presynaptic membrane was accompanied by a more convoluted appearance of the postsynaptic spine surface.…”
Section: Cltp-induced Formation Of Small Spines At Hippocampal Mossy mentioning
confidence: 95%
See 1 more Smart Citation
“…On the postsynaptic side, we observed an increase in the complexity of the large spines or excrescences in contact with MFBs. In particular, we observed the formation of small, filopodia-like protrusions originating from the large complex spines (Zhao et al, 2012a,b). Thus, the more labyrinthine course of the presynaptic membrane was accompanied by a more convoluted appearance of the postsynaptic spine surface.…”
Section: Cltp-induced Formation Of Small Spines At Hippocampal Mossy mentioning
confidence: 95%
“…Following TEA treatment and incubation in control medium, respectively, the tissue was immediately shock-frozen using an EM PACT2 high-pressure freezer from Leica Microsystems (Vienna). The material was then subjected to cryosubstitution and embedding in Epon or Lowicryl HM20 (Zhao et al, 2012a,b; Studer et al, 2014). Epon embedding was used for studies on structural changes at spine synapses, whereas Lowicryl embedding was preferred in immunogold labeling experiments.…”
Section: Cltp-induced Formation Of Small Spines At Hippocampal Mossy mentioning
confidence: 99%
“…In particular, a complicated interaction between glutamatergic ionotropic receptors (AMPA and NMDA) and actin, a main structural element in the spine (Fifkova and Delay, 1982; Matus et al, 1982), has been observed in a number of studies. Activation of AMPA receptors during LTP increases d h (Fischer et al, 2000; Zhao et al, 2012a, b) and this increase is attributed to the stabilization of spines through actin-dependent mechanisms (Fischer et al, 2000) or to a change in the balance between the filament (F-actin) and monomer (G-actin) forms of actin (Zhao et al, 2012a). This would imply that changes in AMPA receptor activation drive the changes in spine morphology.…”
Section: 1 Enduring Drug-induced Synaptic Plasticity: Alterations Imentioning
confidence: 99%
“…LTP can be evoked by intense electrical or chemical stimulation, in the latter case, through the application of extracellular potassium (Bernard et al 1994;Roisin et al 1997), tetraethylammonium (TEA) or 4-aminopyridine (Bancila et al 2004;Suzuki and Okada 2009). Cell depolarization evoked by external potassium that can stimulate simultaneously all mossy fiber synapses (Zhao et al 2012), and/or high external zinc, combined or not with potassium, evoked intracellular zinc enhancements in cultured cortical neurons and in hippocampal slices (Sensi et al 1997;Marin et al 2000;Ketterman and Li 2008). On the other hand, it has been shown that TEA evokes mossy fiber LTP causing also an inhibition of synaptic activity due to zinc binding to presynaptic K ATP channels (Bancila et al 2004;Suzuki and Okada 2009).…”
Section: Introductionmentioning
confidence: 99%